Finite-time backstepping control with command filter for a class of nonlinear systems with parametric uncertainties. (August 2020) - Feng, Cong; Wang, Qing; Hu, Changhua; Zhang, Shen
In this paper, the problem of adaptive finite-time control is considered for a class of nonlinear systems with parametric uncertainties. A novel adaptive command filtered backstepping control method is proposed, and the adverse impact caused by the command filter is eliminated by introducing modified error compensation mechanism with consideration of parametric uncertainties. Combined with the designed adaptation laws, the error compensation mechanism can be finite-time stable. Rigorous proof is achieved to show that the tracking error converges to a small neighborhood of zero in finite time with online parameters adaptation and error compensation. Finally, numeral simulations are presented to validate the effectiveness of the proposed adaptive finite-time control scheme.